Interaction Effect of Social Isolation and High Dose Corticosteroid on Neurogenesis and Emotional Behavior - Chan, Jackie N.-M.; Lee, Jada C.-D.; Lee, Sylvia S. P.; Hui, Katy K. Y.; Chan, Alan H. L.; Fung, Timothy K.-H.; Sánchez-Vidaña, Dalinda I.; Lau, Benson W.-M.; Ngai, Shirley P.-C. (Frontiers in Behavioral Neuroscience, 2017)
Hypercortisolemia is one of the clinical features found in depressed patients. This clinical feature has been mimicked in animal studies via application of exogenous corticosterone (CORT). Previous studies have suggested that CORT can induce behavioral disturbance in anxious-depressive like behavior, which is associated in relations with suppressed neurogenesis. Hippocampal neurogenesis plays an important role in adult cognitive and behavioral regulation. which iIts suppression may thus lead to neuropsychiatric disorders. Similar to the effects of CORT on the animals’ depression-like behaviors and neurogenesis, social deprivation has been regarded as one of the factors that predicts poor prognosis in depression. Furthermore, social isolation is regarded as a stressor to social animals including experimental rodents. Hence, this study aims to examine if social isolation would induce further emotional or anxiety-like behavior disturbance and suppress neurogenesis in an experimental model that was repeatedly treated with corticosterone (CORT). Sprague-Dawley rats were used in this study to determine the effects of different housing conditions, either social isolated or group housing, in vehicle-treated control and CORT-treated animals. Forced swimming test (FST), open field test (OFT) and social interaction test (SIT) were used to assess depression-like, anxiety-like and social behaviors respectively. Immunohistochemistry was performed to quantify the number of proliferative cells and immature neurons in the hippocampus, while dendritic maturation of immature neurons was analyzed by Sholl analysis. Interestingly, an interaction effect between social isolation and corticosterone treatment on behavioral tests and neurogenesis was found. Social isolation reduced immobility time in FST and proliferating cells in the hippocampus under CORT-treated condition. Similar effects was also observed in the neurogenesis assay, where the ratio of doublecortin and BrdU positive cells was reduced in CORT-treatment under isolated condition. The current findings suggested that the behavioral and neurological effect of social isolation is dependent on the condition of hypercortisolemia. Furthermore, social isolation may possibly augment the signs and symptoms of depressed patients with potential alteration in neurogenesis.